2014
DOI: 10.7314/apjcp.2014.15.21.9467
|View full text |Cite
|
Sign up to set email alerts
|

Status of Oxidative Stress and Antioxidant Levels in Smokers with Breast Cancer from Western Nepal

Abstract: Background: Research indicates that oxidative stress induced by smoking plays a role in breast cancer. In view of these reports, we aimed to study th relationship between smoking and oxidative stress in breast cancer patients from the western region of Nepal. Materials and Methods: The study included a control group of 42 females (non-smoking healthy women) and a test group sudivided into Group I consisting of 46 female breast cancer patients who were smokers and Group II consisting of 42 non-smoking breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…SVCT-2 levels were shown to correlate with ascorbate uptake and to influence chemo-sensitivity in breast cancer cells in vitro [59]. Low plasma ascorbate levels have been documented in breast cancer patients, with levels as low as 15 μM [60] or 36 μM being reported [6164]. In contrast, plasma levels in the general population average 50 μM, with levels above 70 μM being indicative of plasma saturation [6568].…”
Section: Discussionmentioning
confidence: 99%
“…SVCT-2 levels were shown to correlate with ascorbate uptake and to influence chemo-sensitivity in breast cancer cells in vitro [59]. Low plasma ascorbate levels have been documented in breast cancer patients, with levels as low as 15 μM [60] or 36 μM being reported [6164]. In contrast, plasma levels in the general population average 50 μM, with levels above 70 μM being indicative of plasma saturation [6568].…”
Section: Discussionmentioning
confidence: 99%
“…The reliance on dietary intake in humans can therefore lead to deficiency if adequate intake is not maintained and this is pertinent to the effects of ascorbate supplementation in cancer. Turnover appears to be accelerated during periods of illness ( Bonham et al, 1999 ; Fain et al, 2003 ; Gan et al, 2008 ; Evans-Olders et al, 2010 ) and, although information is sparse, many cancer patients are found to be ascorbate deficient when measurements have been made ( Anthony and Schorah, 1982 ; Ray and Husain, 2001 ; Mayland et al, 2005 ; Shah et al, 2009 ; Badid et al, 2010 ; Nagamma et al, 2014 ). These low plasma levels are likely to correlate with lower tissue levels; this has been demonstrated in white blood cells ( Levine et al, 2001 ) and in a mouse model of ascorbate dependency low plasma levels resulted in almost complete tissue deficiency ( Vissers et al, 2011 ).…”
Section: Uptake and Metabolism Of Ascorbatementioning
confidence: 99%
“…The relationship between oxidative stress parameters and a history of smoking and drinking is contradictory. A significant rise in oxidative stress and low levels of antioxidants has been observed in breast cancer patients with a smoking history [ 27 ]. However, smoking and alcohol consumption did not modify the effect of the oxidative stress-modifying genes in pancreatic cancer [ 28 ], and no significant interaction was observed between pack-years of smoking and oxidative stress-related genetic polymorphisms in colorectal cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%